A sleeping tiger ethnicity, class, and new Dayak dreams in urban Sarawak - Boulanger, Clare L. (University Press of America, 2009)
A Sleeping Tiger is a rare book-length treatment of urbanization among Dayaks and also offers a fresh perspective on ethnicity, class, and the context in which they function to the benefit of some and the great detriment of others.